2021
DOI: 10.1177/2150135120975761
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Diagnosis of ALCAPA Complicating an Aortopulmonary Window Repair

Abstract: We present the case of transient left ventricular dysfunction secondary to impaired left coronary artery filling after aortopulmonary window repair, caused by intraoperative diagnosis of anomalous left coronary artery from pulmonary artery. Immediate recognition and repair allowed for uneventful recovery of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…We thank Professor Anderson for his comments on our paper wherein we discussed the challenges faced during the management of a patient with anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) associated with aortopulmonary window (APW). 1 As acknowledged in our report, a handful of cases with a similar combination are available in literature. In addition, Prof Anderson proposes, based on his relentless observations, that there might be an embryologic plausibility for the occurrence of coronary arterial malformation in hearts with persistent aortopulmonary foramen.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We thank Professor Anderson for his comments on our paper wherein we discussed the challenges faced during the management of a patient with anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) associated with aortopulmonary window (APW). 1 As acknowledged in our report, a handful of cases with a similar combination are available in literature. In addition, Prof Anderson proposes, based on his relentless observations, that there might be an embryologic plausibility for the occurrence of coronary arterial malformation in hearts with persistent aortopulmonary foramen.…”
supporting
confidence: 62%
“…In 2 recent case reports published in the journal, attention has been drawn to the association between an aortopulmonary window and anomalous origin of the left coronary artery from the pulmonary trunk. 1,2 In the manuscript recently listed as an “online first,” Arvind et al 2 go so far as to suggest that their observation of this combination is “unique.” This seems somewhat of an exaggeration since in the text they cite the earlier report. 1 This report itself acknowledged the previous account provided by Alhadlaq et al, 3 which revealed the presence of at least 11 known cases.…”
mentioning
confidence: 99%
“…Failure to identify and correct this coronary anomaly during surgery for associated lesions would result in unforeseen postoperative ventricular dysfunction. 3,4…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report by Bourlon et al only 12 patients have been reported in literature with this unusual combination of APW and ALCAPA. [2][3][4] Of these, preoperative identification of ALCAPA was accomplished in one patient only, suggesting the challenges in Submitted August 20, 2021; Accepted October 28, 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation